2018
DOI: 10.3389/fneur.2018.00715
|View full text |Cite
|
Sign up to set email alerts
|

Grafting Neural Stem and Progenitor Cells Into the Hippocampus of Juvenile, Irradiated Mice Normalizes Behavior Deficits

Abstract: The pool of neural stem and progenitor cells (NSPCs) in the dentate gyrus of the hippocampus is reduced by ionizing radiation. This explains, at least partly, the learning deficits observed in patients after radiotherapy, particularly in pediatric cases. An 8 Gy single irradiation dose was delivered to the whole brains of postnatal day 9 (P9) C57BL/6 mice, and BrdU-labeled, syngeneic NSPCs (1.0 × 105 cells/injection) were grafted into each hippocampus on P21. Three months later, behavior tests were performed. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…Herein, we investigated the effects of metformin pretreatment (preTx) in a model of juvenile cranial IR 8 that involves a clinically relevant dose of IR (8 Gy) 45 and age (postnatal day 17 [P17]). 5 , 46 Using an in vitro NSC colony-forming assay (neurosphere assay), we assessed the effects of metformin preTx and cranial IR on the activated NSC (aNSC) pool (i.e., colony-forming NSCs in vitro ) 47 and quantified neurogenesis and microglia activation along the SEZ-OB neurogenic axis in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Herein, we investigated the effects of metformin pretreatment (preTx) in a model of juvenile cranial IR 8 that involves a clinically relevant dose of IR (8 Gy) 45 and age (postnatal day 17 [P17]). 5 , 46 Using an in vitro NSC colony-forming assay (neurosphere assay), we assessed the effects of metformin preTx and cranial IR on the activated NSC (aNSC) pool (i.e., colony-forming NSCs in vitro ) 47 and quantified neurogenesis and microglia activation along the SEZ-OB neurogenic axis in vivo .…”
Section: Introductionmentioning
confidence: 99%
“…Yet they showed again that the IntelliCages were able to recognize systematic group effects in partially noisy and uncontrollable environments. Of note, however, is that IntelliCages were used later to reveal irradiation-induced behavioral changes ( Barlind et al, 2010 ; Karlsson et al, 2011 ; Huo et al, 2012 ; Roughton et al, 2012 ; Ben Abdallah et al, 2013 ; Kalm et al, 2013 , 2016 ; Osman et al, 2014 ; Kato et al, 2018 ; Sato et al, 2018 ).…”
Section: Review Bodymentioning
confidence: 99%
“…It has been shown that UCB‐SC treatment plays a neural‐restorative and neural‐regenerative role in premature brain injuries (Sun & Kurtzberg, ) (Figure ). Some UCB‐SCs likely differentiate into “replacement” glial cells and neurons and integrate into the host brain where they play a role in re‐myelination (Sato et al, ; Shen et al, ). In addition, UCB‐SCs might enhance blood vessel regeneration (Kourembanas, ), and an increasing number of studies have indicated that UCB‐SCs migrating to the site of brain injury might provide restorative and neuroprotective factors or endogenous cell signals to injured host neural cells via the paracrine activity of immune factors, anti‐inflammatory cytokines such as IL‐8 and IL‐10 (Nazmi et al, ; Xia et al, ), and neurotrophic factors such as neurotrophin‐3/4, brain‐derived neurotrophic factors, glial‐derived neurotrophic factor, vascular endothelial growth factor, hepatocyte growth factor, and insulin‐like growth factor‐1, which support neuronal migration, proliferation, and differentiation and promote angiogenesis (Bennet et al, ; Drobyshevsky et al, ; Geisler, Dinse, Neuhoff, Kreikemeier, & Meier, ; Hellstrom et al, ; Rosenkranz & Meier, ).…”
Section: Mechanisms Of Ucb‐sc Therapymentioning
confidence: 99%